PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KARTUN FISIKA TERHADAP MOTIVASI BELAJAR MAHASISWA PADA MATA KULIAH FISIKA TERAPAN - Evin Yudhi Setyono (Politeknik Negeri Bali, 2014)
The purpose of this research is to study the effect of physics cartoon on motivation of PNB civil engineering students in applied physics subject. Questioner is given before and after lecturing process. The result of descriptive statistic shows that experiment class get light increasing of mean score from 78,20 to 78,92 , while control class shows decreasing from 79,04 to 76,20. The final motivation score of experiment class is higher than control class, which is 78,92 and 76,20 respectively. Furthermore, independent sample t-test by SPSS 19 results there is no significant motivation difference between both class. So, it is concluded that the use of physics cartoon as a learning media in a physics lecture has no significant effect on students motivation.